Modified neuroimmune processes and emotional behaviour in weaned and late adolescent male and female mice born via caesarean section - Mathieu Di Miceli; Moïra Rossitto; Maud Martinat; Flore Marchaland; Sarah Kharbouche; Marion Graland; Farah Younes; Alexandra Séré; Agnès Aubert; Lydia Rabbaa Khabbaz; Charlotte Madore; Jean-Christophe Delpech; et al. (Scientific Reports)
Abstract Elective and emergency Caesarean section (C-section) procedures are on the rise, exceeding the recommended guidelines by the World Health Organization. Higher morbidities and long-term health conditions are correlated to C-section deliveries, including neurodevelopmental disorders. During C-section delivery, newborns are not exposed to the vaginal commensal flora, which impedes the early establishment of the gut microbiota. The latter is essential for adequate neuro-immune processes to take place during infancy. In this study, we used a validated model of mice born by C-section (CSD), which mimics clinical observations of dysregulated gut microbiota. Animals were either born naturally or by CSD, before being adopted by dams who underwent delivery within the 12 preceding hours. Behavioural analyses were conducted at post-natal day (PND) 21 and 55. Our results indicate that animals born by C-section present significantly higher body weight in late (PND40-P53) but not early adolescence (PND21-P27), compared to animals born by vaginal delivery (VD). Male animals delivered by C-section presented significantly lower exploration time of the novel arm in the Y Maze test at PND55. However, at PND21, abnormal social interaction was witnessed in male and female animals born by CSD, with significantly decreased time spent interacting during the social interaction test. At both PND21 and PND55, animals from both sexes born by C-section presented significantly decreased time spent in the open arm of the Elevated Plus Maze test, compared to control animals. We then measured the expression of genes associated to neuroimmune interactions (microglia phenotype), inflammatory mediators and lipids in several brain structures of VD and CSD mice at PND21 and PND55. At weaning, animals born by CSD presented altered microglia, inflammatory and lipid metabolism signatures, with increased expression of Cd36, Csf1r and Tnfα in different brain regions of males, but not in females. At PND64, Csf1r, Tmem119 as well as C3ar1 were significantly increased in males born by C-section, but not in females. In males born by vaginal delivery, the expression of Cd36 at PND64 was correlated to anxiety at PND55, whilst a correlation between the expression of Clec7a and the number of head dippings in the elevated plus maze was also noted in males born by CSD. Altogether, our study shows altered emotional behaviour in animals delivered by CSD, which is likely explained by underlying neuro-inflammatory processes in different brain regions. Our work further supports the long-term consequences of CSD on brain health.